Cancer metabolism control by natural products: Pyruvate kinase M2 targeting therapeutics. (6th July 2022) - El‐Far, Ali H.; Al Jaouni, Soad K.; Li, Xiaotao; Fu, Junjiang
Abstract: Glycolysis is the primary source of energy for cancer growth and metastasis. The shift in metabolism from mitochondrial oxidative phosphorylation to aerobic glycolysis is called the Warburg effect. Cancer progression due to aerobic glycolysis is often associated with the activation of oncogenes or the loss of tumor suppressors. Therefore, inhibition of glycolysis is one of the effective strategies in cancer control. Pyruvate kinase M2 (PKM2) is a key glycolytic enzyme overexpressed in breast, prostate, lung, colorectal, and liver cancers. Here, we discuss published studies regarding PKM2 inhibitors from natural products that are promising drug candidates for cancer therapy. We have highlighted the potential of natural PKM2 inhibitors for various cancer types. Moreover, we encourage researchers to evaluate the combinational effects between natural and synthetic PKM2 inhibitors. Also, further high‐quality studies are needed to firmly establish the clinical efficacy of natural products.